From Omnichannel Shopping Experience to Purchase Decision Among Indonesian Consumers : A Moderated Mediation Model - Nurjannah, Nurjannah; Ridjal, Syamsul; Idris, Muh. Maruf; Alam, Syamsul (International Review of Management and Marketing, 2026)
This study investigates how omnichannel shopping experience and digital engagement influence purchase decisions by incorporating trust as a mediator and perceived data security as a moderator. Drawing on the Stimulus–Organism–Response (S-O-R) framework, digital engagement and shopping experience are conceptualized as external stimuli that shape consumer trust, which subsequently drives purchase decisions in omnichannel retail contexts. Data were collected from 200 consumers with prior omnichannel shopping experience and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that omnichannel shopping experience significantly influences both trust and purchase decision, while trust has a strong positive effect on purchase decision. In contrast, digital engagement does not directly affect purchase decision. However, digital engagement significantly influences trust, indicating an indirect-only mediation effect through trust. Furthermore, perceived data security strengthens the relationship between trust and purchase decision, confirming its moderating role. These results highlight that purchase decisions in omnichannel retailing are primarily driven by seamless experiences and trust-building mechanisms rather than digital engagement alone. The study provides theoretical and managerial insights into how retailers can enhance conversion through trust and data security assurance.